2002
DOI: 10.1111/j.1749-6632.2002.tb04794.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Pathology and Dementia in Autopsied Honolulu‐Asia Aging Study Participants

Abstract: Clinicopathologic data from 285 autopsies were analyzed. The decedents were long-standing participants in the Honolulu-Asia Aging Study, a prospective epidemiologic investigation of stroke, neurodegenerative diseases, and aging. We assessed the prevalence at death of four primary neuropathologic processes using specific microscopic lesions as indicators. An algorithm was developed to assign each decedent to one of six subsets, corresponding to pathologic dominance by microvascular lesions (14% of decedents), A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
305
3
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(329 citation statements)
references
References 13 publications
16
305
3
5
Order By: Relevance
“…In view of the above considerations, we have examined our data to see if the assertion arising from the Honolulu Asian Ageing Study, that microinfarcts are of particular significance as predictors of clinically expressed SVD, is justified in this cohort 10. We show that the inclusion of microinfarcts does modestly increase the number of brains examined to which a diagnosis of SVD can be assigned using our criteria.…”
Section: Discussionmentioning
confidence: 98%
“…In view of the above considerations, we have examined our data to see if the assertion arising from the Honolulu Asian Ageing Study, that microinfarcts are of particular significance as predictors of clinically expressed SVD, is justified in this cohort 10. We show that the inclusion of microinfarcts does modestly increase the number of brains examined to which a diagnosis of SVD can be assigned using our criteria.…”
Section: Discussionmentioning
confidence: 98%
“…2,7 In the neuropathologic literature, there is no consensus on the definition of the size of a CMI. Some studies report an upper limit for CMI size as 'microscopic' or 'not visible to the naked eye,' but several studies also classify lesions up to a few mm in size as CMIs.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies found microinfarcts only in the watershed areas (Suter et al, 2002;Strozyk et al, 2010), others only in the cortical gray matter (Olichney et al, 1997;Lee et al, 2000). White et al (2002) found cortical microinfarcts mostly located toward the base of the gray matter, while Okamoto et al (2009) described them mostly in the superficial layers of the cortex.…”
Section: Distribution Of Microinfarctsmentioning
confidence: 99%
“…The most commonly used neuropathological criteria for AD were the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) (Mirra et al, 1991) and the Braak criteria (Braak and Braak, 1991). Fifteen studies (41%) primarily classified the patients on clinical criteria (Erkinjuntti et al, 1988;Vinters et al, 2000;Xuereb et al, 2000;White et al, 2002;Gold et al, 2007;Sonnen et al, 2007;Schneider et al, 2007a, b;Strozyk et al, 2010;Troncoso et al, 2008;White, 2009;Wang et al, 2009;Brayne et al, 2009;Ghebremedhin et al, 2010;Sinka et al, 2010;Arvanitakis et al, 2011). The Diagnostic and Statistical Manual of Mental Disorders (American Psychiatric Association, 2000) was used most frequently, followed by the Cognitive Assessment Screening Instrument (Teng et al, 1994).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation